THE SOCIAL IMPLICATIONS OF DECARBONISING THE NEW ZEALAND ECONOMY. - Chapman, Ralph; Boston, Jonathan (Social Policy Journal of New Zealand, 2007)
There is strong evidence that the mean surface temperature of the Earth has risen significantly since 1900. Recent evidence suggests that, if warming of more than 2°C (above pre-industrial levels) is to be avoided, then the emissions of greenhouse gases by developed countries, like New Zealand, may need to fall by up to 70% by 2030 and 90% by 2050. Achieving such a rapid decarbonisation will require major changes in energy generation, transport fuels and behaviour, land use and urban design, underpinned by modifications to national policy frameworks, and changes in social attitudes and behaviour. This paper outlines the case for rapid decarbonisation, assesses the implications for New Zealand's economy and society, discusses the required policy changes and the likely economic and distributional impacts of such changes, and explores institutional factors influencing policy development and implementation. The paper draws on recent international and domestic studies of the likely economic and distributional impacts of policy measures to mitigate climate change. It also refers to some survey evidence concerning public attitudes towards climate change and the willingness of citizens to change their behaviour and support policy measures to reduce emissions.